THE EFFECT OF SEX EDUCATION AND LIFE SKILLS FOR PREVENTIVE SEXUAL RISK BEHAVIOURS AMONG UNIVERSITY OF STUDENTS THAILAND - Seangpraw, Katekaew; Somrongthong, Ratana; Choowanthanapakorn, Monchanok; Kumar, Ramesh (Journal of Ayub Medical College Abbottabad, 2017)
Background: Currently, the problem of sexual risk behaviour of adolescents has increased worldwide, including Thailand. This study compared the effectiveness of promoting life skills to prevent sexual risk behaviours among university students in the Phayao Province of Thailand. Methods: A quasi-experimental design was employed with a pre- and post-test study for a sample of freshmen university students. The students were then split into an intervention group comprised of 300 students, with a second group of 250 students from the same faculty as the control group. The intervention group participated in the integrated life skills model for preventing sexual risk behaviours and participatory learning. The educational activities included; lectures, brainstorming, group discussion, role-playing, game simulations and naming experiences through six weekly life skills training sessions of 90 minutes each. Data were collected by self-questionnaires and analysed using descriptive statistics and independent sample t-testing. Three different time periods were examined using ANOVA repeated measures analysis of variance. Results: Compared between the intervention and control groups determined that implementation of increased knowledge and improved life skills was statistically significant (p<0.001) in the intervention group. The intervention group also showed significantly improved communication skills and behavioural preventive measures towards sexual risk than the control group (p<0.001). Conclusion: The life skills model also effectively reduced the sexual risk behaviours of students at the university. Therefore, this program was beneficial for the development of strategies to increase self-efficacy and it should be integrated into the universities' curriculum. In the long-term sexual risk behaviour changes must be monitored for programme sustainability. Keywords: Sex education; Life skills; Preventive sexual risk behaviours